Makna Kebahagiaan bagi Wanita Karir yang Berkeluarga - Diah Puspita Sari; Rakhmaditya Dewi Noorrizki (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
This study aims to determine the meaning of happiness for career women who already have families. This study uses a qualitative method with a phenomenological model. The participants in this study were three women with the criteria of having a job and being married. The data collection technique used was semi-structured interview. The data analysis used was a phenomenological analysis technique, while checking the validity of this study was done by checking participants. The results of this study are that participants have their own meaning of happiness about their lives which can be seen from several aspects, namely the hedonic influence, satisfaction, and the dominant influence. The participants felt happy by carrying out two roles simultaneously, namely as a wife and a career woman.